Drag decomposition of a subsonic wing via a far-field, exergy-based method - Logothetis, Dimitrios K.; Zachos, Pavlos K.; Rogero, Jean-Michel (SAGE, 2022)
This paper focuses on the aerodynamic analysis and drag decomposition of an unpowered, low aspect ratio wing, using a far-field, exergy-based method. As opposed to traditional drag accounting methods, exergy balance provides insights into the amount of energy that can be potentially recovered off the body’s wake, which further translates into potential efficiency gains of the integrated engine-wing system. In this study, a far-field exergy balance method was used to determine the total drag of a three-dimensional wing. The far-field drag prediction was verified against near-field calculations. In addition, drag decomposition using exergetic terms was conducted to identify drag components that contain possibly recoverable energy. Such analysis can be subsequently used to educate the integration of a propulsion system to exploit the potentially recoverable wake energy and deliver an integrated engine-wing system with enhanced installed efficiency. The present methodology is a major step ahead in the application of far-field methods on three-dimensional wake domains and can potentially become a major enabler for optimal propulsion integration for future, novel aircraft-engine configurations.
Keywords: Exergy Balance method; far-field drag calculation; wing-tip vortex; induced drag; aerodynamics; CFD; subsonic wings; wake recuperation